KONTRIBUSI ULAMA PATANI TERHADAP PERKEMBANGAN HADIS - Ilham Ramadan Siregar (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2021)
ABSTRACT Pattani is one of the Muslim majority areas in Thailand, there are many scholars who are influential in the religious field. Among them are Sheikh Abdullah bin Abdul Mubin, Sheikh Wan Hasan bin Wan Ishak and those who appeared in the 20th century were Dr. Jihad Fathullah, as for the purpose of this study is to determine the contribution of these scholars in the field of Hadith. Therefore the authors examine their works, relevant previous research, as well as various literacies that discuss the thoughts of the three scholars. The result of this research is knowledge about the contribution of Abdullah bin Abdul Mubin in the field of hadith study is to translate the book Tanbih al-Gafilin and he is the first translator of the book Tanbih al-Gafilin into Malay, the contribution of Syeikh Wan Hasan bin Wan Ishak is writing the book of Hidayat. al-Mukhtar, a translation of the Hadith Arba'in and also wrote a translation of the book Ayyuha al-Walad by Imam al-Gazali, while Dr. Jihad Fathullah made a monumental work, namely, Syarah Bulug al-Maram min Adillat al-Ahkam a book of syarah Hadith from the book Bulug al-Maram. ABSTRAK Pattani adalah salah satu wilayah mayoritas Muslim yang terdapat di Negara Thailand, terdapat banyak ulama yang berpengaruh dalam bidang keagamaan. Adapun diantaranya adalah Syeikh Abdullah bin Abdul Mubin, Syekh Wan Hasan bin Wan Ishak dan yang muncul di abad ke 20 adalah Dr. Jihad Fathullah, adapun tujuan penelitian ini adalah untuk mengetahui kontribusi ulama-ulama tersebut di bidang Hadis. Oleh karena itu penulis meneliti karya karya mereka, penelitian terdahulu yang relevan, serta berbagai literasi yang membahas tentang pemikiran ketiga ulama tersebut. Hasil dari penelitian ini adalah pengetahuan tentang kontribusi Abdullah bin Abdul Mubin di bidang kajian hadis adalah membuat terjemah kitab Tanbih al-Gafilin dan dia merupakan penerjemah kitab Tanbih al-Gafilin yang pertama kedalam bahasa Melayu, kontribusi Syeikh Wan Hasan bin Wan Ishak adalah menulis kitab Hidayat al-Mukhtar, sebuah terjemahan dari Hadis Arba‘in dan juga menulis terjemah dari kitab Ayyuha al-Walad karya Imam al-Gazali, sedangkan Dr Jihad Fathullah membuat sebuah karya monumentalnya yaitu, Syarah Bulug al-Maram min Adillat al-Ahkam sebuah kitab syarah Hadis dari kitab Bulug al-Maram.